Day of the Flying Fox the true story of World War II pilot Charley Fox - Pitt, Steve (Sandcastle Book, 2008)
Canadian World War II pilot Charley Fox, now in his late eighties, has had a thrilling life, especially on the day in July 1944 in France when he spotted a black staff car, the kind usually employed to drive high-ranking Third Reich dignitaries. Already noted for his skill in dive-bombing and strafing the enemy, Fox went in to attack the automobile. As it turned out, the car contained famed German General Erwin Rommel, the Desert Fox, and Charley succeeded in wounding him. Rommel, who at the time was the Germans' supreme military commander in France orchestrating the Nazis' resistance to the D-day invasion, was never the same after that. Author Steve Pitt focuses on this seminal event in Charley Fox's life and in the war, but he also provides fascinating aspects of the period, including profiles of noted ace pilots Buzz Beurling and Billy Bishop, Jr., and Great Escape architect Walter Floody, as well as sidebars about Hurricanes, Spitfires, and Messerschmitts.